2009
DOI: 10.1080/09687630802128756
|View full text |Cite
|
Sign up to set email alerts
|

Sexual assaults facilitated by drugs or alcohol

Abstract: Over the past 10 years, there has been a rise in the number of reports of drugs being used covertly to incapacitate potential victims for the purpose of sexual assault. However, recent evidence from forensic studies indicates that alcohol is much more commonly implicated in cases of drug facilitated sexual assault (DFSA) when victims are too intoxicated to give consent. Campaigns that warn about the risk of becoming a victim, or even a perpetrator, of sexual assault by excessive use of alcohol are being increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 15 publications
0
3
0
4
Order By: Relevance
“…Furthermore, lethal respiratory depression is a known consequence of acute GHB overdose 19,20 . In addition to voluntary ingestion as a drug of abuse, GHB is misused as a so‐called knockout drug via the rapid occurrence of behavioral alteration effects (e.g., loss of physical control, unconsciousness) following a high‐dosed GHB intake 15,21–24 . In cases of drug‐facilitated crimes (e.g., drug‐facilitated sexual assault [DFSA]), the frequently arising anterograde amnesia of the victims as well as the short detection window (maximum 6–8 h in blood and maximum 10–12 h in urine) and major interindividual and intraindividual variations of endogenous GHB concentrations complicate the analytical proof of GHB administration 15,25–29 …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, lethal respiratory depression is a known consequence of acute GHB overdose 19,20 . In addition to voluntary ingestion as a drug of abuse, GHB is misused as a so‐called knockout drug via the rapid occurrence of behavioral alteration effects (e.g., loss of physical control, unconsciousness) following a high‐dosed GHB intake 15,21–24 . In cases of drug‐facilitated crimes (e.g., drug‐facilitated sexual assault [DFSA]), the frequently arising anterograde amnesia of the victims as well as the short detection window (maximum 6–8 h in blood and maximum 10–12 h in urine) and major interindividual and intraindividual variations of endogenous GHB concentrations complicate the analytical proof of GHB administration 15,25–29 …”
Section: Introductionmentioning
confidence: 99%
“…Among victims of sexual assault in our sample, roughly 36% reported a single incident, 46% reported two or three, and 18% reported four or more; thus, 64% of victims had experienced more than one sexual assault. Most commonly reported were incidents of incapacitated sexual assault, where the victim voluntarily consumed drugs or alcohol prior to victimization (see Lawyer et al, 2010;Monk & Jones, 2014;Olszewski, 2009); the level or degree of intoxication prior to assault remains unclear from the present work. Overall, findings provide support for Hypotheses 1, substance-related assaults occurred more frequently than forcible sexual assaults; however, Lawyer et al (2010) found a larger differential between forcible sexual assaults and substance-related assaults at roughly a 1:5 ratio, whereas we found a 2:3 ratio.…”
Section: Discussionmentioning
confidence: 87%
“…Örneğin; İngiliz Suç Tarama araştırmasına göre cinsel saldırıya uğrayanların % 5'i istemsiz bir biçimde madde etkisindeyken cinsel saldırıya uğradıklarını belirtirken, % 15'i cinsel ilişki için gereken rızayı gösteremeyecek kadar yüksek oranlarda alkol etkisi altında olduklarını belirtmişlerdir (Olszewski, 2009). Ayrıca, Amerika Birleşik Devletleri'nde telefon kanalıyla gerçekleştirilen cinsel saldırı odaklı bir çalışmada katılımcıların % 2,3'ü alkol veya psikoaktif maddeler ile kendi kendilerini istemli bir biçimde etkisiz hale getirdiklerini ve faillerin de bu durumlarını kullandıklarını bildirmişlerdir (Kilpatrick, Resnick, Ruggiero, Conoscenti ve McCauley, 2007).…”
Section: Alkol Ve Kolaylaştırıcı Maddelerunclassified